Hubungan Stres dan Pola Makan dengan Kejadian Gastritis pada Santri di Pondok Pesantren Bangkalan Madura - Auliya Ulfa; Wulandari , Atik Sri; Wiradinata, Harsono (Calvaria Medical Journal, 2026)
Background: Gastritis or ulcer disease is a condition when the inner layer (mucosa) of the stomach wall experiences inflammation or swelling. Objectives: This study aims to determine the relationship between stress and diet with incidence gastritis in students at the Bangkalan Madura Islamic Boarding School. Methods: The design of this study uses a descriptive analytical case control approach. Result: The results of the research that has been conducted on 95 respondents divided into case groups (gastritis) amounting to 47 respondents and 48 respondents were in the control group (non-gastritis). The results of the analysis showed that most of the students experienced very heavy stress, namely 21 respondents (22.1%), while in the diet, most of them experienced a lack of diet category, a total of 56 respondents (58.9%). Meanwhile, the results of the Chi Square stress statistical test obtained a value of 0.005 with a significance level of 0.05. The test criteria are that the null hypothesis (H0) is rejected if < 0.05. Because the value in the statistical test was greater than 0.05, H0 was rejected, which means that there was a significant relationship between stress and the incidence of gastritis in students. Also, in the results of the Chi Square stress statistical test, a value of 0.001 was obtained with a significance level of 0.05, which can be concluded that there is a relationship between diet and the incidence of gastritis in students. Conclusions: The conclusion of this research is that very severe stress and poor diet can trigger gastritis in students at the Bangkalan Madura Islamic boarding school, Bancaran Bangkalan. It is hoped that this research can be a reference for students and pesantren to evaluate diets and activities that are too dense to be able to prevent the occurrence of gastritis.